Isolated falciparum ligament necrosis causing right upper quadrant pain - Yavuz Savaş Koca; Nazan Okur; İbrahim Barut (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Koca YS, Okur N, Barut İ. Isolated falciparum ligament necrosis causing right upper quadrant pain. Turk J Gastroenterol 2017; 28: 531-2.